Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

High-coverage paleo-genome research identifies a pathogenic mutation on EXT1 in a Qing-period Chinese individual with multiple osteochondromas - Bangyan Wang; Haodong Chen; Fanhao Xi; Haoquan Bao; Hetong Wen; Panxin Du; Chenshuang Sun; Jianxue Xiong; Baoshuai Zhang; Xin Chang; Yawei Zhou; Chuan-Chao Wang; et al. (Molecular Genetics and Genomics, 2026)

Limosilactobacillus reuteri Y15 enhances uterine development and function in gilts via the gut-uterus axis - Juanli Huo; Shen Li; Dongxin Lu; Lei Li; Weidong Zhang; Yukang Li; Bin Yao; Yong Zhao; Yawei Zhang; Jie Zhang; Huiying Luo (Theriogenology, 2026)

Synergistic enhancement of microalgal fatty acids via Batch Bayesian Optimization-driven combinatorial additive engineering - Yu Zhao; Yawei Wu; Guopeng Chen; Shi Guo; Fangzhong Wang; Lei Chen; Weiwen Zhang; Jie Chen (Bioresource Technology, 2026)

Isolation and identification of tropical source Lactobacillus plantarum CK3 and its effects on fatty liver in laying hens - Yongzhen Chen; Xinyu Feng; Xinyi Zhang; Andrea Abreo Medina; Jiayu Feng; Xin Li; Meiyu Duan; Yawei Qiu; Fang Gan (Research in Veterinary Science, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Photocatalytic inhibition and mechanisms of adult Ulva prolifera by COF-supported CuS under visible light - Yingqi Zhang; Qingying Wei; Yun Tian; Yawei Zhang; Linqing Cui; Renjun Wang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2026)

Nitrogen sources and concentrations shape algal odor compounds: Key drivers of β-cyclocitral and β-ionone in water bodies of the lower Yangtze River - Sicheng Yin; Youyin Hu; Yawei Xing; Xianyun Wang; Erik Jeppesen; Liqing Wang; Wei Zhang (Journal of Environmental Sciences, 2026)

Structural changes of costameres and actomyosin induced by postmortem resonant stimulation - Wanhong He; Yingbo Peng; Haixia Huang; Hao Wen; Chuanfeng Liu; Zhenzhen Li; Yawei Zhang (Food Research International, 2026)

Seasonal shifts in dissolved organic matter composition drive the formation of nitrogenous disinfection byproducts via a carbon-nitrogen coupling mechanism in source water - Tianyu Chen; Shiyang Yu; Qiurui Zhang; Jing Qian; Yonghong Bi; Anen He; Lingxiangyu Li; Nanwen Zhu; Jitao Lv; Zhigang Li; Yawei Wang; Guibin Jiang (Environmental Research, 2026)

Urban–rural divergence of wintertime organic aerosol molecular fingerprints in PM2.5 revealed by FT–ICR MS - Shanshan Tang; Jintian Zhang; Yuansheng Wang; Jitao Lv; Lei Liu; Weijun Li; Yawei Wang (Atmospheric Environment, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

A functional lactic acid bacteria strain that naturally produces hydroxytyrosol and its impact on the antioxidant activity and post-acidification of fermented milk - Panpan Han; Yangliu Liu; Min Zhang; Yinglin Chen; Simiao Zhai; Zhixin Wang; Yawei Ning; Yingmin Jia (Food Bioscience, 2026)

Consistency and specificity of soil and microbial responses among crops to mulching practices in semi-arid rainfed agroecosystems in China - Yao Zhang; Yuwei Chai; Xichen Wang; Hongbo Cheng; Yawei Li; Jiantao Ma; Lei Chang; Shouxi Chai (European Journal of Agronomy, 2026)

Multi-mode and encapsulated droplet-based electricity generator for environmental sensing and cathodic protection - Miaomiao Cui; Peiyu Wu; Ruiqi Fang; Wenbo Zhao; Yuankai Jin; Yawei Feng; Fuhui Wang; Zhipeng Zhang; Xiangyu Li; Dake Xu (Chemical Engineering Journal, 2026)

Cross-scale mechanisms and molecular–ecological thresholds of phthalate stress in the cucumber–soil system - Zhe Li; Lei Wang; DongDong Tuo; FuXin Huang; YaWei Shi; Ying Zhang (Journal of Hazardous Materials, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Optical properties and sources of water-soluble brown carbon in PM2.5 at an island site in the Pearl River Estuary: Assessing continental and marine influences - Yawei Xue; Yuan Gao; Jianbo Ye; Qianyun Zhong; Cheng Zhang; Yee Jun Tham (Atmospheric Pollution Research, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prenatal Chromium Exposure and Gestational Diabetes Mellitus: Integrating Genetic and Epigenetic Regulation of LPCAT1 from a Phospholipid Remodeling Perspective - Yuxin Tian; Lu Yao; Jiaqi Zhang; Meng Zhou; Yue Dou; Bole Zhang; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang; Weiwei Wu (Biological Trace Element Research, 2026)

HILPDA, Regulated by WTAP in an m6A-Dependent Manner, Enhances Osteosarcoma Development by Inhibiting Ferroptosis and Promoting Glycolysis - Yong Jing; Guoyong Zhang; Chenghui Sun; Yawei Pan; Jun Tuo; Zhi Li; Chengji Jiang; Zejian Qiu; Qin Lou (Biochemical Genetics, 2026)

Efficient removal of N-nitrosodimethylamine and triclosan by nFe@Fe3O4 nanocomposites: Enhanced generation of active hydrogen atoms - Ying Han; Wanqing Zhao; Xiaoping Zheng; Chuwei Li; Lingyun Tang; Tengfei Zhang; Yawei Xie; Hongyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

Functional Lactiplantibacillus plantarum MT213 screened from traditional sourdough and its promising in-situ preservation in steamed bread - Danya Tong; Yajuan Zhang; Tianyi Zhang; Zhixin Wang; Shijie Wang; Xueming Xu; Yawei Ning (International Journal of Food Microbiology, 2026)

Scale-dependent divergent response of soil respiration and its variation under grazing and reduced precipitation in a sandy Pinus sylvestris var. mongolica plantation - Zi Li; Xu Han; Hengming Zhang; Jiang Zhao; Xiang Li; Guochuang Zhang; Yawei Wei; Shengjin Qin (Journal of Soils and Sediments, 2026)

Integrating electronic sensory, untargeted metabolomics, and FT-NIR spectroscopy with machine learning for rapid origin discrimination and quality assessment of Chebulae Fructus - Yuhang Li; Wei He; Hanwen Zhang; Yue'e Li; Xiaomeng Li; Guokan Ge; Yawei Huang; De Ji (Food Research International, 2026)

Soluble dietary fibers as structuring agents in gelatin gelation: Effects on phase behavior, network formation, water mobility, and colorant stability in low- and high-solid matrices - Ruican Wang; Yawei Chang; Richard W. Hartel; Ying Zhang; Shuo Wang (Food Hydrocolloids, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Human thermal responses to non-uniform cooling from intermittently operated split air conditioners - Haiyan Yan; Yawei Li; Thomas Parkinson; Stefano Schiavon; Hui Zhang; Ruiji Sun; Shengkai Zhao; Wei Zhao; Zhen sun; Fangning Shi (Building and Environment, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Untargeted metabolomics-based investigation of amino acid effects on antimicrobial peptides production in Paenibacillus ehimensis HD 8-3 fermentation - Chengling Feng; Jiapei Zhang; Yunfei Si; Zhen Zhao; Yawei Ning; Zhixin Wang (Food Bioscience, 2026)

Comparative assessment of physicochemical and functional properties of chestnut protein obtained by different extraction methods - Haoxin Cui; Yazhou Ji; Yawei Chang; Zhenting Yu; Fan Wei; Bowei Zhang; Yingshuang Lu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

One-step rapid synthesis Ti-O-rich Ti3C2 MXene via NH4HF2 hydrothermal etching for high charge storage - Xuefeng Sha; Xianyin Song; Qiwei Shangguan; Yawei Lv; Fan Zeng; Xingang Zhang; Xueli Wu; Minghao Yu; Changzhong Jiang (Chemical Engineering Journal, 2026)

Novel enhanced network integrating transformations of DOM and microorganisms (ENITM) elucidates microbial-driven transformation pathways in estuarine sediments - Shiyang Yu; Jitao Lv; Xindong Ma; Lu Jiang; Qiurui Zhang; Tianyu Chen; Han Fang; Dong Cao; Lixia Zhao; Yawei Wang (Water Research, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

An ensemble method for integrating rainfall forecast products based on average mutual information decomposition - Wei Ding; Minglei Ren; Yawei Ning; Xuan Li; Jinnan Zhang; Huicheng Zhou (Environmental Modelling & Software, 2026)

Hepatocellular carcinoma with microvascular invasion: from theory to clinical practice - Tong Yuan; Yawei Fan; Honghao Zhou; Chengjian Shi; Qi Cheng; Erlei Zhang (Science China Life Sciences, 2026)

Co-liquefaction of triacetyl cellulose (TAC) from waste LCDs and high-sulfur low-rank coal (HSLC) by sub/supercritical water: Synergistic effect, desulfuration, and resource recovery - Fu-Rong Xiu; Yawei Ju; Yan Zhang; Jiaqing Hu; Yingying Qi (Waste Management, 2026)

Performance analysis of seismic mitigation by replacing foundation soil with a periodic structure for nuclear power structures considering SSI - Zequan Sun; Yawei Duan; Mi Zhao; Zhidong Gao; Di Yao; Lihua Wu; Guoliang Zhang; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Spatial distribution and ecological risk assessment of pharmaceuticals and personal care products across China's coastal waters - Jia Shao; Tianyu Chen; Lu Jiang; Jitao Lv; Jingyu Zhang; Dan Wu; Fenfen Zhang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Anthropogenic filtering of detrital zircon and rutile signals in the Yangtze River: Implications for provenance reconstruction - Rujun Guo; Xianyan Wang; Xilin Sun; Wencke Wegner; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Urs Klötzli; Chang'an Li (Global and Planetary Change, 2026)

Cardiac targeted delivery of Maresin 1 nanomedicine rescues microvascular obstruction after myocardial infarction - Yawei Zhao; Jing Zhang; Xiaohan Fan; Yue Cai; Wenting Du; Ziyi Yu; Biao Xu; Xuan Sun (Chemical Engineering Journal, 2026)

Morphological and functional analysis of saccus vasculosus of mandarin fish ( Siniperca chuatsi ) - Rahma Sakina Said Aly; Jiajie Fang; Keying Li; Xiao Ma; Jiong Gao; Meng Zhang; Xiaowu Chen; Yawei Shen (Journal of Fish Biology, 2026)
The saccus vasculosus (SV) is a specialized periventricular organ found in some species of teleost and elasmobranch fishes, located at the back of the hypothalamus and pituitary gland. However, its function remains incompletely understood. In this study, histological, transmission electron microscopy (TEM) and transcriptomic analyses were employed to investigate the SV of the mandarin fish ( Siniperca chuatsi ) to gain insights into its morphology, gene expression profile and function. Through histological staining techniques, different cell types within the SV can be identified and characterized. The SV is highly folded vascularized neuroepithelium and is deeply connected to blood vessels. TEM studies showed that the capillaries that produced the lumen formed complex narrow channels are linked to the third ventricle of the hypothalamus. The bright neuroepithelium is formed by coronet cells and supporting glial cells, interspersed with liquor‐containing neurons, while the dark contrast is attributed to the presence of heavy elements such as calcium. We identified 28 specific genes in SV, which are most enriched in the purine metabolism pathway, including the genes of pde9al , pde9ac , pde6hl and sgc88el . Gene Ontology biological process analysis for the SV‐specific genes showed that response to osmotic stress was the hub term according to the enrichment maps. Additionally, SV‐specific genes opsin ( opsin8b ), photoreceptor ( pcare1 ) and aquaporin ( aqp4 , aqp9l ) of Siniperca chuatsi may indicate that they play a role as a sensor of season and are involved in osmoregulation. This study, the first on the Siniperca chuatsi , suggests that the SV may have unique physiological functions in teleost fish.

Molecular-scale mechanism of extracellular protein over-flocculation for sewage sludge dewatering by polyacrylamide - Minmin Liu; Jiesi Zhang; Yawei Zhao; Wei Wang; Huihui Zhang; Wenzheng Yu (Water Research, 2025)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

Efficient removal of nitrogen, phosphorus and antibiotics in freshwater aquaculture wastewater using a novel hybrid aeration biological filter - Dongyu Xia; Weina Dou; Yawei Tian; Lei Zhang; Cai Wang; Yong Wang; Jingyi Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xiang Mei (Journal of Environmental Management, 2025)

The inhibitory potential effect of CMC-Na on PhIP, Harman, and Norharman formation in low-NaCl fried beef patties under repeated freeze-thaw cycles - Yi Zhao; Pinghua Deng; Keying Zhang; Ruoxi Ma; Shuang Teng; Yawei Zhang (Food Chemistry, 2025)

Unraveling the complex gelation dynamics of gelatin solutions mixed with various mono-, di-, or trisaccharides: A comparative study based on hydration properties - Ruican Wang; Yawei Chang; Yuanyifei Wang; Richard W. Hartel; Ying Zhang; Liye Zhu; Dancai Fan; Shuo Wang (Food Hydrocolloids, 2025)

A study on a correction method for channel wave energy consistency under geophone-bolt coupling - Guangzhong Ji; Lingyun Shi; Yawei Zhang; Shuai Xu; Keyue Liu (Acta Geophysica, 2025)

Microbial-mediated transformation shapes the molecular diversity of landfill leachate under anthropogenic and natural covariation - Qiurui Zhang; Jitao Lv; Shiyang Yu; Tianyu Chen; Yue Sun; Feifei Li; Lu Bai; Xianwei Wang; Xiaosong He; Yong Nie; Nanwen Zhu; Yawei Wang; et al. (Water Research, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Dual-action mechanism of Tamarix polyphenols in inhibiting IQ and MeIQ: Synergistic scavenging of free radicals and trapping of reactive carbonyls - Xiaopu Ren; Bing Xie; Mingyang Li; Shuai Kang; Wei Wang; Qianqian Yu; Yawei Zhang; Lujuan Xing (Food Chemistry, 2025)

Transcriptome to reveal the immunological defenses in mandarin fish (Siniperca chuatsi) skin with LPS and poly (I:C) infection - Yawei Shen; Jiong Gao; Meng Zhang; Yongjing Li; Rahma Sakina Said Aly; Lei Wang; Miao Yu; Hongxia Jiang; Zhigang Qiao; Xiaowu Chen (Fish & Shellfish Immunology, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Tuning electrode wettability to optimize nanobubble nucleation and reaction rates in water electrolysis - Zhenlei Wang; Yaxi Yu; Mengkai Qin; Hao Jiang; Zhenjiang Guo; Lu Bai; Limin Wang; Xiaochun Zhang; Xiangping Zhang; Yawei Liu (Chemical Engineering Journal, 2025)

Dual roles of N6-methyladenosine in R-loop regulation of gene transcription and genome stability - Fangle Li; Feifan Zhang; Jie Li; Yu Zhang; Wenxuan Gong; Yawei Zhang; Mengxia Liu; Jie Ren; Dali Han (Science China Life Sciences, 2025)

Numerical study on transient unloading fracture mechanism of deep hard rock under 3D stress path induced by drilling and blasting - Weiqi Wang; Yawei Zhang; Rui Kong; Qihu Wang; Yulong Zhang (Bulletin of Engineering Geology and the Environment, 2025)

The effect of fluid saturation on the elastic properties of coal measure rocks under confining pressure - Fei Gong; Guangui Zou; Suping Peng; Zhaoji Zhang; Hao Chen; Yawei Zhao (Journal of Applied Geophysics, 2025)

Flexible erythritol-based spatiotemporal phase change films with multiple energy responses for wearable thermal management - Huimin Yan; Yan Kou; Shihui Zhang; Hanqing Liu; Nan Yin; Yawei Xu; Quan Shi (Chemical Engineering Journal, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

Graphene/epoxy coating with radiation heat dissipation properties for spacecraft thermal management - Ning Li; Yibo Zhang; Yawei Xu; Jing Li (Chemical Engineering Journal, 2025)

Mediating role of whole epigenome DNA methylation signatures in the association between copper and SGA - Weiwei Wu; Mengru Wang; Shan Li; Bole Zhang; Weixuan Hu; Yulin Li; Yongliang Feng; Yawei Zhang; Suping Wang (Journal of Trace Elements in Medicine and Biology, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

The inhibition potentiality of sodium carboxymethyl cellulose on PhIP, Harman, and Norharman formation of fried beef patties at low NaCl level - Yi Zhao; Pinghua Deng; Ruoxi Ma; Shuang Teng; Hang Lu; Zheng Liu; Haotian Yu; Yawei Zhang (Meat Science, 2025)

Thermo-responsive hydrogel evaporator via In-Situ chromogenic strategy for high-efficiency solar desalination with robust salt resistance - Ju Lv; Lang Pan; Yawei Zhu; Xinyue Zhang; Liujin Yang; Xiudie Wang; Xueqiong Yin (Chemical Engineering Journal, 2025)

Gram-scale synthesis of unsupported Pt-rare earth nanosponge for enhanced stability in proton exchange membrane fuel cells - Chenhao Li; Hao Wang; Fangren Qian; Yawei Li; Qinqin Sang; Qingjun Chen; Jialiang Liao; Yihan Zhu; Yanrong Liu; Suojiang Zhang (Chemical Engineering Journal, 2025)

Quaternary ammonium COF-based proton exchange membranes for enhanced electrochemical hydrogen compression - Xiao Pang; Ziwen Liu; Shuting Xu; Kexin Lv; Benbing Shi; Xu Dong; Na Xing; Zhong Gao; Shiyi Zhu; Leilang Zhang; Zengguang Yao; Lijuan Cheng; et al. (Chemical Engineering Journal, 2025)

Water erosion control through vegetation restoration: Mechanisms and contributions of vegetation components in Robinia Pseudoacacia forests - Yang Li; Yawei Hu; Jiongchang Zhao; Jianjun Zhang (CATENA, 2025)

Measurement and modeling of canopy interception loss of evergreen, deciduous and mixed forests in a subhumid watershed on the Loess Plateau, China - Jiongchang Zhao; Yang Yu; Yawei Hu; Matthias Beyer; Jianjun Zhang (Journal of Hydrology, 2025)

Anti-inflammatory effect of food bioactives in inflammatory bowel disease: Role of the gut microbiome - Yawei Zhang; Lufan Zhang; Yang Dong; Yunwei Yang; Mengxing Li; Qian Chen; Dan Wang; Yuzheng Wu; Tao Wang (Food Bioscience, 2025)

Pathways of 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) inhibited by basic amino acids in the glucose/ creatinine/ phenylalanine model system - Pinghua Deng; Yi Zhao; Shuang Teng; Keying Zhang; Yawei Zhang (Food Chemistry, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Modeling of non-grouted interlocking brick masonry using rigid-body-spring model - Yanan Lu; Lihua Huang; Xihong Zhang; Tingwei Shi; Yawei Zhu (Engineering Structures, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

A Comprehensive Review of Ship Automatic Rudder Technology: Development, Challenges, and Prospects - Minjie Zheng; Qianqiang Chen; Daowei Yan; Yawei Zhang (Journal of Marine Science and Engineering, 2025)
Ship automatic rudder systems are critical to enhancing the precision, safety, and intelligence of modern navigation, which plays a significant role in optimizing vessel control, reducing crew workload, and improving operational efficiency. First, this paper undertakes a meticulous analysis of the evolution of automatic rudder technology research through the application of bibliometric analytical methodologies. Second, a thorough literature review is conducted, focusing on the fundamental components of automatic rudder technology, encompassing sensor technologies, control algorithms, and basic functionalities, including both the latest advancements and the distinct traits of various technological approaches and algorithms. Third, the core functions of automatic rudder technology are analyzed, which includes heading control, wave compensation, ship collision avoidance, safety control mechanisms, path planning, and tracking control. Lastly, this paper summarizes the principal challenges encountered during the development of automatic rudder technology and proposes potential directions for future advancements.

Genome-wide association study reveals growth-related mutations and candidate genes at early growth stages in largemouth bass (Micropterus salmoides) - Xiao Ma; Dongcai Chen; Zhilin Jia; Yue Xu; Zhigang Qiao; Lei Wang; Hongxia Jiang; Miao Yu; Yongjing Li; Xiaotian Gao; Chunlong Zhao; Yawei Shen; et al. (Aquaculture, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Serum concentrations of persistent endocrine-disrupting chemicals in U.S. military personnel: A comparison by race/ethnicity and sex - Karl C. Alcover; Jordan McAdam; Hristina Denic-Roberts; Celia Byrne; Andreas Sjodin; Mark Davis; Richard Jones; Yawei Zhang; Jennifer A. Rusiecki (International Journal of Hygiene and Environmental Health, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Nuclear receptor 4A1 inhibits chondrocyte inflammation and cartilage degeneration in osteoarthritis by inhibiting NF-κB signal pathway - Yawei Zhang; Hengheng Zheng; Baitong Li (Inflammopharmacology, 2025)

The Combined Effect Between SEPS1 Genetic Polymorphisms and Exposure to Metals on the Risk of Gestational Diabetes Mellitus - Weiwei Wu; Yulin Li; Weixuan Hu; Jing Zhao; Bole Zhang; Yongliang Feng; Yawei Zhang; Suping Wang (Biological Trace Element Research, 2025)

Accurate prediction of pollution and health risks of iodinated X-ray contrast media in Taihu Lake with machine learning and revealing key environmental factors - Xinying Cheng; Yuteng Zhang; Sirui Yan; Qingsong Ji; Xiangcheng Kong; Huiming Li; Shiyin Li; Shaogui Yang; Zhigang Li; Yawei Wang; Limin Zhang; Huan He (Water Research, 2025)

Study on the deterioration of bond-slip performance of rockbolt grouted structures under corrosion - Shuisheng Yu; Shucan Lu; Yawei Wang; Hongsen Zhang; Fuzhou Qi (Computers and Geotechnics, 2025)

Wood-derived closed pore hard carbon encapsulated micro-sized silicon anode design for long-term practical lithium-ion battery - Yingzhe Gao; Kai Zhang; Xiaohang Du; Guihua Liu; Yawei Du; Jingde Li (Chemical Engineering Journal, 2025)

Impact of surface reservoir construction on groundwater circulation and recharge in the Yangzhuang karst groundwater system, China - Yawei Feng; Fengxin Kang; Bintao Liu; Lichuan Zhang; Zhifeng Li; Xuetao Xing; Qingcheng He (Hydrogeology Journal, 2025)

Genome-wide association analysis study on host resistance against the Aeromonas veronii of largemouth bass Micropterus salmoides - Meng Zhang; Xiao Ma; Zerui Wang; Yuqing Han; Zhilin Jia; Dongcai Chen; Yue Xu; Zhigang Qiao; Xinyu Jiang; Lei Wang; Hongxia Jiang; Miao Yu; et al. (Fish & Shellfish Immunology, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

A hybrid TCN-BiLSTM short-term load forecasting model for ship electric propulsion systems combined with multi-step feature processing - Shuo Pang; Liang Zou; Li Zhang; Hui Wang; Yawei Wang; Xingdou Liu; Jundao Jiang (Ocean Engineering, 2025)

Polysaccharide-gated metal–organic framework nanoparticles for pH-triggered site-specific delivery and enhanced fungicide bioavailability - Chunlin Yang; Yawei Tang; Xiang Yao; Peijie Hu; Zaiyu Lu; Jinjing Xiao; Lihong Zhang; Haiqun Cao (Chemical Engineering Journal, 2025)

Effects of traffic noise on the psychophysiological responses of college students: An EEG study - Nan Zhang; Chao Liu; Menglin Zhang; Yawei Guan; Wenhua Wang; Zihao Liu; Weijun Gao (Building and Environment, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

Ultrasensitive and high selectivity detection of fibrin using Y-shaped DNA-homing peptide doped probe on localized surface plasmon resonance platform - Yawei Chen; Yuanfu Zhang; Xue Zhao; Wenyu Xu; Shuhao Wang (Analytica Chimica Acta, 2025)

Hedge three-dimensional reconstruction and motion control technology for trimming robot - Jin Gu; Bin Zhang; Yu Wang; Yawei Zhang (Computers and Electronics in Agriculture, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Pressure retarded osmosis enhanced by micro-nano bubbles: Coupling effects of operation conditions and mass transfer resistance analyses - Yawei Du; Jiangbo Dai; Wuao Zhou; Lijin Ma; Jingxin Wei; Lixin Xie; Huining Deng; Shaofeng Zhang (Desalination, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Discovery of the Miocene Yuanmou Conglomerate and Its Significance for the Drainage Evolution in the Southeastern Tibetan Plateau - Dai Zhang; Chang’an Li; Shitao Zhang; Honglin Yuan; Zengjie Zhang; Yawei Li (Journal of Earth Science, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

Construction method and case study of digital twin system for combine harvester - Yanxin Yin; Bowen Ma; Zhijun Meng; Liping Chen; Mengnan Liu; Yawei Zhang; Bin Zhang; Changkai Wen (Computers and Electronics in Agriculture, 2024)

The effect of anthropogenic activities on the behavior of novel brominated flame retardants in surface soil of Northern China urbanized zone - Ziyan Liu; Yaqi Zhang; Feifei Li; Huifang Zhong; Runzeng Liu; Qiu Zhang; Rongguang Shi; Yingjun Wang; Yawei Wang (Science of The Total Environment, 2024)

Microstructural evolution and mechanics behavior of postmortem meat subjected to resonance - Yingbo Peng; Shujie Liu; Wanhong He; Boqun Liao; Yawei Zhang (Journal of Food Engineering, 2024)

Comprehensive characterization of the differences in metabolites, lipids, and volatile flavor compounds between Ningxiang and Berkshire pigs using multi-omics techniques - Qian Wang; Hu Gao; Yawei Fu; Yue Chen; Gang Song; Zhao Jin; Yuebo Zhang; Jie Yin; Yulong Yin; Kang Xu (Food Chemistry, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

Optimal conditions for cryopreservation by vitrification of largemouth bass (Micropterus salmoides) embryos - Meng Zhang; Xiao Ma; Yuqing Han; Zerui Wang; Zhilin Jia; Dongcai Chen; Zhigang Qiao; Xiaotian Gao; Chunlong Zhao; Yawei Shen (Animal Reproduction Science, 2024)

CoAl-Layered Double Hydroxide Catalytic Membrane for Activation of Peroxymonosulfate Towards Efficient Degradation of Organic Pollutants - Yawei Shi; Tongwen Zhang; Qian Chang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2024)

Effects of basic amino acids on heterocyclic amines and quality characteristics of fried beef patties at low NaCl level - Pinghua Deng; Shuang Teng; Yu Zhou; Yuling Liu; Boqun Liao; Xiaopu Ren; Yawei Zhang (Meat Science, 2024)

Inactivation mechanism of phenyllactic acid against Bacillus cereus spores and its application in milk beverage - Dongchun Zhang; Danya Tong; Zhixin Wang; Shijie Wang; Yingmin Jia; Yawei Ning (Food Chemistry, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Enhanced treatment of pyridine wastewater by a hybrid membrane biofilm reactor: Simultaneous biodegradation of pyridine and removal of nitrogen - Jingyi Zhang; Yawei Tian; Zhan Wang; Mengmeng Yang; Yong Wang; Han Gao; Zimiao Zhang; Yutong Han; Yanyan Xiao; Xu Yang; Xuanwei Zhao; Yue Wu; et al. (Process Safety and Environmental Protection, 2024)

Investigating functional mechanisms in the Co-biodegradation of lignite and guar gum under the influence of salinity - Bing Li; Hongyu Guo; Ze Deng; Linyong Chen; Changjiang Ji; Xiaokai Xu; Yawei Zhang; Song Cheng; Zhenzhi Wang (Journal of Environmental Management, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Exogenous iron caused osteocyte apoptosis, increased RANKL production, and stimulated bone resorption through oxidative stress in a murine model - Zengfeng Guo; Jiawen Wu; Yawei Hu; Jianhua Zhou; Qingmei Li; Yandong Zhang; Junde Zhang; Linbo Yang; Shenghang Wang; Hao Zhang; Jiancheng Yang (Chemico-Biological Interactions, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Rutile and zircon U-Pb dating as a constraint on sedimentary provenance of the Jianchuan Basin: Implications for paleo-drainage evolution - Rujun Guo; Xilin Sun; Chang'an Li; David Chew; Foteini Drakou; Zengjie Zhang; Yawei Li; Chuanyi Wei; Taorui Zeng; Jiranan Homnan; Urs Klotzli (Geomorphology, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

A real-time accuracy prediction model on time-relative positioning method considering the correlation of position increment errors - Xuan Zou; Zhiyuan Li; Weiming Tang; Yawei Wang; Yangyang Li; Siyu Zhang; Yongfeng Zhang (GPS Solutions, 2024)

The application of chitosan quaternary ammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering - Minmin Liu; Sajid Rashid; Wei Wang; Huihui Zhang; Yawei Zhao; Xingmin Fu; Zhaoyang Su; Nigel Graham; Wenzheng Yu (Water Research, 2024)

Long‒term trends in surface thermal environment and its potential drivers along the urban development gradients in rapidly urbanizing regions of China - Chengyu Zhao; Hongkai Zhu; Shuyi Zhang; Ziwen Jin; Yiwen Zhang; Yawei Wang; Yadie Shi; Jianhui Jiang; Xiaoyong Chen; Min Liu (Sustainable Cities and Society, 2024)

Experimental study on the dynamic responses of harbour seal whiskers in the wake of caudal fin - Hanghao Zhao; Zhimeng Zhang; Weilin Chen; Yawei Zhao; Edward Yaw Sefah; Chunning Ji; Dekui Yuan (Ocean Engineering, 2024)

Experimental study on flow-induced vibrations of an equilateral triangular prism with a high mass ratio - Yawei Zhao; Zhimeng Zhang; Chunning Ji; Hanghao Zhao; Weilin Chen (Ocean Engineering, 2024)

Efficient degradation of organic pollutants with sodium percarbonate by activation with CuFeS2 prepared from precursors of different valence states - Yawei Shi; Qian Chang; Tongwen Zhang; Zonglin Pan; Ruisong Xu; Ya Sun; Guanghui Ding (Journal of Environmental Chemical Engineering, 2024)

Process optimization of high purity CO2 compression and purification system from oxygen-rich combustion flue gas - Lijin Ma; Yawei Du; Xiaojun Guo; Wuao Zhou; Huining Deng; Shaofeng Zhang (International Journal of Greenhouse Gas Control, 2024)

An impact of l-histidine on the phosphorylation and stability of pyruvate kinase at low NaCl level - He Wanhong; Peng Yingbo; Wang Wenqi; Jamali Muneer Ahmed; Teng Shuang; Peng Zengqi; Zhang Yawei (Food Chemistry, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Characteristics of advanced anaerobic digestion sludge-based biochar and its application for sewage sludge conditioning - Qian Chen; Xingmin Fu; Jiawei Wang; Yawei Zhao; Wei Wang; Abdul Ghaffar Memon; Huihui Zhang; Yang Wen (Bioresource Technology, 2024)

Effects of Dietary Valine Chelated Zinc Supplementation on Growth Performance, Antioxidant Capacity, Immunity, and Intestine Health in Weaned Piglets - Tuan Zhang; Nan Zhang; Shuyu Peng; Yawei Zhang; Huakai Wang; Shiyu Huang; Min Zhu; Yongxi Ma (Biological Trace Element Research, 2024)
This study was conducted to investigate the effects of dietary valine chelated zinc (ZnVal) supplementation on growth performance, antioxidant capacity, immunity, and intestine health in weaned piglets. A total of 240 healthy 35-day-old weaned piglets (Duroc × Landrace × Yorkshire, average weight 10.70 ± 0.14 kg) were randomly divided into five groups with six replicate pens and eight piglets per pen. Dietary treatments were a corn–soybean meal basal diet supplemented with 0, 25, 50, 75, and 100 mg/kg ZnVal, respectively. The experiment lasted for 28 days. Results showed that average daily gain (ADG) was increased ( P < 0.05) by ZnVal with 75–100 mg/kg supplementation on days 15–28 and with 50–100 mg/kg supplementation on days 1–28. Supplementation of 25–100 mg/kg ZnVal reduced ( P < 0.01) the diarrhea rate of weaned piglets on days 1 to 14 and 1 to 28. Dietary supplementation with 25–100 mg/kg ZnVal increased ( P < 0.05) copper/zinc-superoxide dismutase (Cu/Zn-SOD) and decreased malonaldehyde (MDA) activities in the serum on day 14 and 28. Supplementation of 25–100 mg/kg ZnVal increased ( P < 0.05) glutathione peroxidase (GSH-Px) activity in serum on day 14. Additionally, the supplementation of 75 mg/kg ZnVal significantly increased the activity of superoxide dismutase (SOD) and Cu/Zn-SOD in the liver ( P < 0.05). Furthermore, the supplementation of 25–100 mg/kg ZnVal significantly increased the total antioxidant capacity (T-AOC) in the liver ( P < 0.05). Higher ( P < 0.05) concentrations of IgG in the serum were measured from piglets supplemented with 75–100 mg/kg ZnVal on day 14 and dietary supplementation with 25–100 mg/kg ZnVal increased the level of immunoglobulin G (IgG) in serum on day 28 ( P < 0.05). In addition, higher ( P < 0.05) concentrations of immunoglobulin A (IgA) in the duodenum and ileum were measured from piglets supplemented with 75 mg/kg ZnVal and the supplementation of 25–100 mg/kg ZnVal also showed a higher ( P < 0.05) concentration of immunoglobulin G (IgG) in duodenum. Supplementation of 50–100 mg/kg ZnVal increased the villus height and villus height/crypt depth of jejunum ( P < 0.05). Moreover, dietary supplementation with 75–100 mg/kg ZnVal showed a higher ( P < 0.05) concentration of zinc in the liver and supplementation of 50–100 mg/kg ZnVal increased ( P < 0.05) the concentration of zinc in the heart, spleen, and kidney. In conclusion, the present research showed that supplementation of ZnVal improves growth performance by increasing antioxidant capacity and immunity and regulating intestinal morphology and the optimal inclusion level of ZnVal was 65~80 mg/kg.

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Degradation metabolic pathway of low-rank coal using single hydrolytic bacteria - Daping Xia; Yunxia Niu; Jixian Tian; Xianbo Su; Guoqin Wei; Kuo Jian; Zhenzhi Wang; Yawei Zhang; Weizhong Zhao (Fuel, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Endocrine disrupting chemical mixture exposure and risk of papillary thyroid cancer in U.S. military personnel: A nested case-control study - Hristina Denic-Roberts; Jordan McAdam; Andreas Sjodin; Mark Davis; Richard Jones; Mary H. Ward; Thanh D. Hoang; Shuangge Ma; Yawei Zhang; Jennifer A. Rusiecki (Science of The Total Environment, 2024)

Criticality assessment of minerals associated with China's battery technologies - Yawei Huang; Peng Wang; Yao Wang; Heming Wang; Yue Zhang; Xiaozhu Xu; Chao Wang; Qiang Yue; Tao Du; Wei-Qiang Chen (Journal of Cleaner Production, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Proteome and gut microbiota analysis of Chinese mitten crab (Eriocheir sinensis) in response to Hepatospora eriocheir infection - Yawei Cao; Leiting Zhang; Yue Yang; Jiaying Li; Xiaoqi Luan; Xiaoli Xia; Wei Gu; Jie Du; Keran Bi; Li Wang; Qingguo Meng (Aquaculture, 2024)

Straw strip mulch improves soil moisture similar to plastic film mulch but with a higher net income - Jiantao Ma; Lei Chang; Yawei Li; Xuemei Lan; Wenning Ji; Jiantong Zhang; Fanxiang Han; Hongbo Cheng; Yuwei Chai; Shouxi Chai (Agriculture, Ecosystems & Environment, 2024)

Comparative transcriptome analysis and genetic dissection of vegetative branching traits in foxtail millet (Setaria italica) - Tianpeng Liu; Xueying Liu; Jihong He; Kongjun Dong; Lei Zhang; Yawei Li; Ruiyu Ren; Tianyu Yang (Theoretical and Applied Genetics, 2024)

New insights into Co3O4-carbon nanotube membrane for enhanced water purification: Regulated peroxymonosulfate activation mechanism via nanoconfinement - Huanran Ma; Guoqing Feng; Xiao Zhang; Chengwen Song; Ruisong Xu; Yawei Shi; Pengcheng Wang; Zhouhang Xu; Guanlong Wang; Xinfei Fan; Zonglin Pan (Chemosphere, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Efficient removal of organic pollutants by activation of peroxydisulfate with the magnetic CoFe2O4/carbon nanotube composite - Yawei Shi; Yi Zhang; Guobin Song; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2023)

Integrating Software FMEA and STPA to Develop a Bayesian Network-Based Software Risk Model for Autonomous Ships - Xue Yang; Yawei Zhu; Tao Zhou; Sheng Xu; Wenjun Zhang; Xiangyu Zhou; Xiangkun Meng (Journal of Marine Science and Engineering, 2023)
The autonomous shipping industry is increasingly focusing on enhancing the safety and reliability of software-based systems. Conducting a risk assessment is a requirement for demonstrating the safety equivalence of autonomous ships based on such systems to conventional vessels. Traditional risk assessment models, however, primarily focus on hardware failures, often overlooking potential software-related failures and functional inadequacies. This study proposes a framework integrating Software Failure Mode and Effects Analysis (FMEA), System–Theoretic Process Analysis (STPA), and Bayesian Network (BN) for risk identification of autonomous ship software systems. The results of a case study reveal that the framework sufficiently addresses the multifaceted nature of risks related to software in autonomous ships. Based on the findings of this study, we suggest the need for standardization of software architecture development in the autonomous ship industry and highlight the necessity for an enhanced understanding of AI-specific risks and the development of tailored risk assessment methodologies.

Mesopore-enhanced graphene electrodes with modified hydrophilicity for ultrahigh capacitive deionization - Ting Yang; Hongmei Zhang; Linpei Guo; Jing Wang; Zhiyuan Guo; Yawei Du; Jie Liu; Yingying Zhao; Panpan Zhang; Zhi-Yong Ji (Desalination, 2023)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Ni-rich cathode materials with enhanced kinetics and hydrophobicity endowed by reactive silane coating - Chi Zhang; Tao Li; Xiangkun Wu; Wei Li; Yawei Guo; Suojiang Zhang; Lan Zhang (Chemical Engineering Journal, 2023)

Investigation with ESI FT-ICR MS on sorbent selectivity and comprehensive molecular composition of landfill leachate dissolved organic matter - Qiurui Zhang; Jitao Lv; Anen He; Dong Cao; Xiaosong He; Lixia Zhao; Yawei Wang; Guibin Jiang (Water Research, 2023)

Absence of known knockdown resistance mutations but fixation of CYP337B3 was detected in field populations of Helicoverpa armigera across China - Ruoyao Ni; Yawei Wang; Qiuzan Zhong; Mei Li; Dandan Zhang; Yongjun Zhang; Xinghui Qiu (Pesticide Biochemistry and Physiology, 2023)

Prenatal polymetallic exposure and small for gestational age: A case-control study in Taiyuan, China - Zhitong Shen; Yue Lu; Zexin Song; Jinbo Li; Wangjun Li; Shan Li; Mengru Wang; Yongliang Feng; Suping Wang; Yawei Zhang; Weiwei Wu (Journal of Trace Elements in Medicine and Biology, 2023)

Monitor water quality through retrieving water quality parameters from hyperspectral images using graph convolution network with superposition of multi-point effect: A case study in Maozhou River - Yishan Zhang; Xin Kong; Licui Deng; Yawei Liu (Journal of Environmental Management, 2023)

An extensive assessment of seasonal rainfall on intracellular and extracellular antibiotic resistance genes in Urban River systems - Wenchao Yu; Ye Xu; YaWei Wang; Qianwen Sui; Yuan Xin; Hui Wang; Junya Zhang; Hui Zhong; Yuansong Wei (Journal of Hazardous Materials, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Developmental Toxicity and Cardiotoxicity Induced by PFOS and its Novel Alternative OBS in Early Life Stage of Zebrafish (Danio rerio) - Dan Yang; Xiaohui Li; Shasha Dong; Xiaohui Zhao; Xiaoying Li; Meng Zhang; Yawei Shi; Guanghui Ding (Water, Air, & Soil Pollution, 2023)

Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery - Xiaoxiao Guo; Siming Chen; Yawei Han; Chunbo Hao; Xiujuan Feng; Baogang Zhang (Journal of Environmental Management, 2023)

Community Characteristics of Soil Ectomycorrhizal Fungi under Different Forests in the Sandy Areas of Northeastern China - Jiaying Liu; Changjun Ding; Weixi Zhang; Yawei Wei; Yongbin Zhou; Wenxu Zhu (Journal of Soil Science and Plant Nutrition, 2023)

Distribution and exposure risk assessment of chlorinated paraffins and novel brominated flame retardants in toys - Ruirui Zhang; Juan Li; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Highly reactive coke made from Low-rank Coal: Relationship between thermal properties and multilevel structure - Xin Zhang; Jun Zhang; Rui Guo; Qiang Xiao; Yawei Feng; Huan Cheng (Fuel, 2023)

Analytical solution for the temperature field of an elliptical tunnel in cold regions - Yanhu Zhao; Jing Zhang; Linjing Li; Taotao Hu; Yawei Zhao (Cold Regions Science and Technology, 2023)

What Drives Migrants Back to Set up Firms? Return-home Entrepreneurial Intention of Rural Migrant Workers in China - Huasheng Zhu; Yawei Chen; Hua Zhang; Zhangfei Liu (Chinese Geographical Science, 2023)

Flood Risk Quantification, Transmission, and Propagation Analysis for Flood Water Utilization of Parallel Reservoirs - Wei Ding; Chi Zhang; Jie Lin; Xi Zhao; Yawei Ning; Huicheng Zhou (Journal of Hydrology, 2023)

Direct absorption of atmospheric lead by rapeseed siliques is the leading cause of seed lead pollution - Junxing Yang; Yawei Yu; Chuang Ma; Hongzhong Zhang (Journal of Hazardous Materials, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Interfacial role of Ionic liquids in CO2 electrocatalytic Reduction: A mechanistic investigation - Shuai Guo; Yawei Liu; Yanlei Wang; Kun Dong; Xiangping Zhang; Suojiang Zhang (Chemical Engineering Journal, 2023)

Effects of Different Levels of Organic Trace Minerals on Oxidative Status and Intestinal Function in Weanling Piglets - Shangchu Wang; Shujun Wu; Yawei Zhang; Juan Chen; Xihong Zhou (Biological Trace Element Research, 2023)

Potential for selective oxidation of aniline in soil washing effluent by active chlorine and testing its practicality - Yi Ren; Xiangxin Meng; Xuan Zhang; Yuhai He; Guangfei Gao; Pengqi Wang; Yawei Gu; Yue Ding; Wenqiang Jiang (Chemosphere, 2023)

Optimal design and operation of reverse osmosis seawater desalination system for boron removal with economic, energy, and environmental concerns - Yawei Du; Xinrong Zhang; Chuanpeng Cao; Jiangbo Dai; Quanyu Gong; Dongxuan Zhang; Huining Deng; Lixin Xie (Desalination, 2023)

Synergistic modification of Ni-rich full concentration gradient materials with enhanced thermal stability - Chi Zhang; Tao Li; Bing Xue; Xiangkun Wu; Liyuan Li; Yawei Guo; Lan Zhang (Chemical Engineering Journal, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Facile Fabrication of Amino Functionalized Magnetic Multi-walled Carbon Nanotubes for Removal of Congo Red from Aqueous Solutions - Guobin Song; Liya Tong; Shuhua Chen; Jing Zhang; Yi Zhang; Haonan Wang; Yawei Shi; Ya Sun; Guanghui Ding (Water, Air, & Soil Pollution, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Twin peaks of in-hospital mortality among patients with STEMI across five phases of COVID-19 outbreak in China: a nation-wide study - Jianping Li; Nan Zhang; Ziyi Zhou; Xiao Huang; Weiyi Fang; Hongbing Yan; Jiyan Chen; Weimin Wang; Dingcheng Xiang; Xi Su; Bo Yu; Yan Wang; et al. (Science China Life Sciences, 2022)

Bone Marrow Mesenchymal Stem Cell-Derived Exosomal microRNA-29b-3p Promotes Angiogenesis and Ventricular Remodeling in Rats with Myocardial Infarction by Targeting ADAMTS16 - Jialin Zheng; Xinjin Zhang; Wenfeng Cai; Yawei Yang; Tao Guo; Jianmei Li; Hualei Dai (Cardiovascular Toxicology, 2022)

DLGAP1-AS2 promotes estrogen receptor signalling and confers tamoxifen resistance in breast cancer - Xiaoli Liang; Yang Zhao; Zeng Fang; Nan Shao; Duanyang Zhai; Mengmeng Zhang; Liang Yu; Yawei Shi (Molecular Biology Reports, 2022)

Magnetic graphene oxide for methylene blue removal: adsorption performance and comparison of regeneration methods - Yawei Shi; Haonan Wang; Guobin Song; Yi Zhang; Liya Tong; Ya Sun; Guanghui Ding (Environmental Science and Pollution Research, 2022)

Water splitting, pollutant degradation and environmental impact using low-index faceted metal-based nanocrystals. A review - Xiang Zhang; Jie Tang; Nali Zhu; Lingxiangyu Li; Yawei Wang (Environmental Chemistry Letters, 2022)

Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.

Design and evaluation of chitosan-amino acid thermosensitive hydrogel - Jianan Tong; Huiyun Zhou; Jingjing Zhou; Yawei Chen; Jing Shi; Jieke Zhang; Xinyu Liang; Tianyuan Du (Marine Life Science & Technology, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Changing incidence and projections of thyroid cancer in mainland China, 1983–2032: evidence from Cancer Incidence in Five Continents - Mandi Li; Jiao Pei; Minghan Xu; Ting Shu; Chengjie Qin; Meijing Hu; Yawei Zhang; Min Jiang; Cairong Zhu (Cancer Causes & Control, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Use of Untargeted Metabolomics to Explore the Air Pollution-Related Disease Continuum - Lan Jin; Krystal J. Godri Pollitt; Zeyan Liew; Ana K. Rosen Vollmar; Vasilis Vasiliou; Caroline H. Johnson; Yawei Zhang (Current Environmental Health Reports, 2021)

Preconception ambient temperature and preterm birth: a time-series study in rural Henan, China - Guoyu Zhou; Meng Yang; Jian Chai; Renjie Sun; Junxi Zhang; Hui Huang; Yawei Zhang; Qihong Deng; Lifang Jiang; Yue Ba (Environmental Science and Pollution Research, 2021)

Winner takes all: reconstructing the decapitation of a warrior in Bronze Age China from osteological evidence - Yawei Zhou; Shuang Lin; Rangping Qin; Hui-Yuan Yeh; Qun Zhang (Archaeological and Anthropological Sciences, 2020)
Decapitation is an ancient practice in Asia with inadequate research. The present study reports on the osteological examination of a headless skeleton excavated from a high-status tomb in Chu State style dating back to the late Warring States Period (ca. 3th century BC) in Lu’an, Anhui, China. The individual is identified as a victim of decapitation with five peri-mortem sharp force cut marks on the posterior parts of the cervical vertebrae, and another one on the right second metacarpal. Microscopic observation of the kerfs, the historical records and archaeological evidence support the speculation that the individual could be a warrior of Chu State, who is decapitated after being wounded during the war against the Qin State. The hacking implement and the sequences of the cut marks are further discussed to reconstruct the process of execution. This multidisciplinary reconstruction is the first scientific osteological analysis of the decapitation on the human remains from the Chinese Bronze Age. Moreover, it will enrich our knowledge of the decapitation phenomenon in terms of war and execution in ancient China.

Neurobehavioral performance of PAH exposure in male coal miners in Shanxi, China: a cross-sectional study - Fang Wang; Liuye Yang; Bin Zhang; Gaisheng Liu; Chongjian Wang; Yawei Zhang; Tong Wang (International Archives of Occupational and Environmental Health, 2020)

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Lithology identification and reservoir characteristics of the mixed siliciclastic-carbonate rocks of the lower third member of the Shahejie formation in the south of the Laizhouwan Sag, Bohai Bay Basin, China - Yajun Duan; Jun Xie; Baichuan Li; Mengqi Wang; Tianqi Zhang; Yawei Zhou (Carbonates and Evaporites, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Antimicrobial Peptide JH-3 Effectively Kills Salmonella enterica Serovar Typhimurium Strain CVCC541 and Reduces Its Pathogenicity in Mice - Lei Wang; Xueqin Zhao; Xiaojing Xia; Chunling Zhu; Wanhai Qin; Yanzhao Xu; Bolin Hang; Yawei Sun; Shijun Chen; Huihui Zhang; Jinqing Jiang; Jianhe Hu; et al. (Probiotics and Antimicrobial Proteins, 2019)

Blood transfusion history and risk of non-Hodgkin lymphoma: an InterLymph pooled analysis - James R. Cerhan; Eleanor Kane; Claire M. Vajdic; Martha S. Linet; Alain Monnereau; Leslie Bernstein; Silvia de Sanjose; Brian C.-H Chiu; John J. Spinelli; L. Dal Maso; Yawei Zhang; Beth R. Larrabee; et al. (Cancer Causes & Control, 2019)

Losartan suppresses the inflammatory response in collagen-induced arthritis by inhibiting the MAPK and NF-κB pathways in B and T cells - Xinming Wang; Xiaoyun Chen; Wei Huang; Pengying Zhang; Yawei Guo; Heinrich Körner; Huaxun Wu; Wei Wei (Inflammopharmacology, 2019)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

Frequency-dependent energy attenuation and velocity dispersion in periodic layered media - Heng Zhang; Fanchang Zhang; Yawei Lu (Acta Geophysica, 2019)

The adsorption behavior of multiple contaminants like heavy metal ions and p-nitrophenol on organic-modified montmorillonite - Yawei Liu; Jingde Luan; Chengyu Zhang; Xin Ke; Haijun Zhang (Environmental Science and Pollution Research, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

A parameter-free progressive TIN densification filtering algorithm for lidar point clouds - Xiaotian Shi; Hongchao Ma; Yawei Chen; Liang Zhang; Weiwei Zhou (International Journal of Remote Sensing, 2018)

Three-dimensional distributed DC/IP method for altered tectonite-type gold ore deposits exploration: a case study of the Jiaojia gold metallogenic belt, Eastern China - Jiayong Yan; Yawei Zhang; Kun Zhang; Yongqian Zhang; Hao Hu; Zhihui Wang (Acta Geophysica, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Mapping the effect of escitalopram treatment on amplitude of low-frequency fluctuations in patients with depression: a resting-state fMRI study - Li Wang; Xueni Li; Ke Li; Yunai Su; Yawei Zeng; Qinge Zhang; Gang Wang; Zhen Jin; Qingmei Kong; Tianmei Si (Metabolic Brain Disease, 2017)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Hyperthermostable Thermotoga maritima xylanase XYN10B shows high activity at high temperatures in the presence of biomass-dissolving hydrophilic ionic liquids - Tianyi Yu; Sasikala Anbarasan; Yawei Wang; Kübra Telli; Aşkın Sevinç Aslan; Zhengding Su; Yin Zhou; Li Zhang; Piia Iivonen; Sami Havukainen; Tero Mentunen; Michael Hummel; et al. (Extremophiles, 2016)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Dynamical analysis of periodic bursting in piece-wise linear planar neuron model - Ying Ji; Xiaofang Zhang; Minjie Liang; Tingting Hua; Yawei Wang (Cognitive Neurodynamics, 2015)

Air Quality in Lanzhou, a Major Industrial City in China: Characteristics of Air Pollution and Review of Existing Evidence from Air Pollution and Health Studies - Yaqun Zhang; Min Li; Mercedes A. Bravo; Lan Jin; Amruta Nori-Sarma; Yanwen Xu; Donghong Guan; Chengyuan Wang; Mingxia Chen; Xiao Wang; Wei Tao; Weitao Qiu; et al. (Water, Air, & Soil Pollution, 2014)

Polymorphisms in DNA repair genes, hair dye use, and the risk of non-Hodgkin lymphoma - Huan Guo; Bryan A. Bassig; Qing Lan; Yong Zhu; Yawei Zhang; Theodore R. Holford; Brian Leaderer; Peter Boyle; Qin Qin; Cairong Zhu; Ni Li; Nathaniel Rothman; et al. (Cancer Causes & Control, 2014)

Role of one-carbon metabolizing pathway genes and gene–nutrient interaction in the risk of non-Hodgkin lymphoma - Qian Li; Qing Lan; Yawei Zhang; Bryan A. Bassig; Theodore R. Holford; Brian Leaderer; Peter Boyle; Yong Zhu; Qin Qin; Stephen Chanock; Nathaniel Rothman; Tongzhang Zheng (Cancer Causes & Control, 2013)

Subtype of dietary fat in relation to risk of Hodgkin lymphoma: a population-based case–control study in Connecticut and Massachusetts - Yongshun Gao; Qian Li; Bryan A. Bassig; Ellen T. Chang; Min Dai; Qin Qin; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

Body size and risk of Hodgkin’s lymphoma by age and gender: a population-based case–control study in Connecticut and Massachusetts - Qian Li; Ellen T. Chang; Bryan A. Bassig; Min Dai; Qin Qin; Yongshun Gao; Yawei Zhang; Tongzhang Zheng (Cancer Causes & Control, 2013)

Smoking, variation in N-acetyltransferase 1 (NAT1) and 2 (NAT2), and risk of non-Hodgkin lymphoma: a pooled analysis within the InterLymph consortium - Todd M. Gibson; Karin E. Smedby; Christine F. Skibola; David W. Hein; Susan L. Slager; Silvia de Sanjosé; Claire M. Vajdic; Yawei Zhang; Brian C.-H. Chiu; Sophia S. Wang; Henrik Hjalgrim; Alexandra Nieters; et al. (Cancer Causes & Control, 2013)

Light at night and breast cancer risk: results from a population-based case–control study in Connecticut, USA - Qian Li; Tongzhang Zheng; Theodore R. Holford; Peter Boyle; Yawei Zhang; Min Dai (Cancer Causes & Control, 2010)

Risk of non-Hodgkin lymphoma and nitrate and nitrite from the diet in Connecticut women - Briseis A. Kilfoy; Mary H. Ward; Tongzhang Zheng; Theodore R. Holford; Peter Boyle; Ping Zhao; Min Dai; Brian Leaderer; Yawei Zhang (Cancer Causes & Control, 2010)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)

Genetic variation in N-acetyltransferases 1 and 2, cigarette smoking, and risk of non-Hodgkin lymphoma - Briseis A. Kilfoy; Tongzhang Zheng; Qing Lan; Xuesong Han; Theodore Holford; David W. Hein; Qin Qin; Brian Leaderer; Lindsay M. Morton; Meredith Yeager; Peter Boyle; Ping Zhao; et al. (Cancer Causes & Control, 2010)

International patterns and trends in thyroid cancer incidence, 1973–2002 - Briseis A. Kilfoy; Tongzhang Zheng; Theodore R. Holford; Xuesong Han; Mary H. Ward; Andreas Sjodin; Yaqun Zhang; Yana Bai; Cairong Zhu; Grace L. Guo; Nathaniel Rothman; Yawei Zhang (Cancer Causes & Control, 2009)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)

Lymphoma survival patterns by WHO subtype in the United States, 1973–2003 - Xuesong Han; Briseis Kilfoy; Tongzhang Zheng; Theodore R. Holford; Cairong Zhu; Yong Zhu; Yawei Zhang (Cancer Causes & Control, 2008)

Genotype frequency and F ST analysis of polymorphisms in immunoregulatory genes in Chinese and Caucasian populations - Qing Lan; Min Shen; Dino Garcia-Rossi; Stephen Chanock; Tongzhang Zheng; Sonja I. Berndt; Vinita Puri; Guilan Li; Xingzhou He; Robert Welch; Shelia H. Zahm; Luoping Zhang; et al. (Immunogenetics, 2007)

Family history of hematopoietic and non-hematopoietic malignancies and risk of non-Hodgkin lymphoma - Yawei Zhang; Rong Wang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Yong Zhu; Qin Qin; Tongzhang Zheng (Cancer Causes & Control, 2007)

Genetic polymorphisms in the oxidative stress pathway and susceptibility to non-Hodgkin lymphoma - Qing Lan; Tongzhang Zheng; Min Shen; Yawei Zhang; Sophia S. Wang; Shelia H. Zahm; Theodore R. Holford; Brian Leaderer; Peter Boyle; Stephen Chanock (Human Genetics, 2007)

Subunit dissociation and stability alteration of d-hydantoinase deleted at the terminal amino acid residue - Lixi Niu; Xueyao Zhang; Yawei Shi; Jingming Yuan (Biotechnology Letters, 2007)

Polymorphisms in DNA repair genes and risk of non-Hodgkin lymphoma among women in Connecticut - Min Shen; Tongzhang Zheng; Qing Lan; Yawei Zhang; Shelia H. Zahm; Sophia S. Wang; Theodore R. Holford; Brian Leaderer; Meredith Yeager; Robert Welch; Daehee Kang; Peter Boyle; et al. (Human Genetics, 2006)

Re: No Increased Risk of non-Hodgkin's Lymphoma with Steroids, Estrogens and Psychotropics (Netherlands) - Tongzhang Zheng; Yawei Zhang; Lindsay Morton; Yong Zhu (Cancer Causes & Control, 2004)

Prior Medical Conditions and Medication use and Risk of non-Hodgkin lymphoma in Connecticut United States Women - Yawei Zhang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Lindsay McOmber Morton; Bing Zhang; Kaiyong Zou; Stuart Flynn; Giovanni Tallini; Patricia H. Owens; Tongzhang Zheng (Cancer Causes & Control, 2004)

Alcohol use and risk of non-Hodgkin's lymphoma among Connecticut women (United States) - Lindsay McOmber Morton; Theodore R. Holford; Brian Leaderer; Yawei Zhang; Shelia Hoar Zahm; Peter Boyle; Stuart Flynn; Giovanni Tallini; Patricia H. Owens; Bing Zhang; Tongzhang Zheng (Cancer Causes & Control, 2003)

Cigarette smoking, glutathione-S-transferase M1 and T1 genetic polymorphisms, and breast cancer risk (United States) - Tongzhang Zheng; Theodore R. Holford; Shelia H. Zahm; Patricia H. Owens; Peter Boyle; Yawei Zhang; John Pierce Wise; Lisa Pleasants Stephenson; Francis Ali-Osman (Cancer Causes & Control, 2002)